Parental self-control and the development of male aggression in early childhood: a longitudinal test of self-control theory - Meldrum, Ryan Charles (International journal of offender therapy and comparative criminology, 2018)
A number of studies have evaluated associations between parenting practices, adolescent self-control, and adolescent antisocial behavior. Yet, few studies have examined associations between these constructs in early childhood or examined the extent to which both maternal and paternal self-control shapes them. To address these gaps, the current study utilizes longitudinal data collected on a sample of 117 Dutch boys and their parents to investigate the across time interrelationships between parental self-control, ineffective parenting, child self-control, and child aggression. The results provide evidence of an indirect association between maternal self-control and early childhood self-control through maternal ineffective parenting, an indirect association between maternal ineffective parenting and early childhood aggression through early childhood self-control, and an indirect association between maternal self-control and early childhood aggression through both maternal ineffective parenting and early childhood self-control. In contrast, paternal self-control and paternal ineffective parenting were unrelated to child self-control and child aggression. The implications and limitations of the study are discussed.